Analysis on intelligent deformation prediction of deep foundation pits with internal support based on optical fiber monitoring and the HSS model - Zhao, Jie; Li, Wenjie; Peng, Yanli (Frontiers in Materials, 2023)
With the continuous expansion of the city scale, while rapidly advancing the foundation pit construction, it has become a top priority to prevent the potential safety hazard caused by efforts to catch up with its deadline. In this case, deep foundation pit monitoring can provide an important technical support for the foundation pit design and construction safety. This paper aims to analyze the characteristics of excavation deformation of deep foundation pit with internal support in Dalian Donggang Business District by combining the method of optical fiber monitoring and finite element simulation. In this study, the distributed optical fiber monitoring and routine monitoring are respectively adopted to carry out the synchronous excavation monitoring of foundation pit support structure. The main monitoring objects are the deep horizontal displacement of the support piles and the surface settlement of foundation pit. Moreover, the author uses the Plaxis finite element software based on the Hardening Soil-small (HSS) model to conduct numerical simulation analysis, and the results are compared with two groups of the measured data of deep foundation pit obtained from the aforementioned researches. Besides, in the light of SSA-BP neural network, the back-analysis method of HSS model parameters in Dalian area is proposed. The findings show that, under the premise of selecting reasonable parameters, the results of finite element analysis of HSS model, considering the small strain characteristics of soil, have a high degree of fit with the actual deformation law of foundation pit, which proves the rationality of the model. Furthermore, it is verified that the distributed optical fiber monitoring has the conspicuous advantages in terms of data continuity and accuracy in contrast to the routine monitoring. The research results of this paper can give reference for the deformation monitoring and early warning of the support structure of deep foundation pit.